2021
DOI: 10.3389/fevo.2021.705318
|View full text |Cite
|
Sign up to set email alerts
|

Egg Cannibalism Varies With Sex, Reproductive Status, and Egg and Nymph Ages in Arma custos (Hemiptera: Asopinae)

Abstract: Background: Egg cannibalism is common in nature. In China, Arma custos (Hemiptera: Asopinae) has been widely used as a natural enemy to control agricultural and forestry pests. A previous study showed that adult A. custos devour their eggs. However, no research has investigated the interaction between A. custos cannibalism and egg development. Clarifying the mechanisms involved in egg cannibalism by A. custos improves our understanding of the evolutionary relationships to enable more efficient mass rearing and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 42 publications
0
2
0
Order By: Relevance
“…As a crucial natural enemy, the predatory stinkbug A. custos has been widely applied to control various agricultural and forestry pests. 44 It was important that the potential adverse impacts of SPc should be assessed before the extensive co-application of the predatory stinkbug and SPc-loaded pesticides. In the current study, the immersion of SPc showed no significant influences on the hatching rate of A. custos eggs.…”
Section: Discussionmentioning
confidence: 99%
“…As a crucial natural enemy, the predatory stinkbug A. custos has been widely applied to control various agricultural and forestry pests. 44 It was important that the potential adverse impacts of SPc should be assessed before the extensive co-application of the predatory stinkbug and SPc-loaded pesticides. In the current study, the immersion of SPc showed no significant influences on the hatching rate of A. custos eggs.…”
Section: Discussionmentioning
confidence: 99%
“…The importance of this insect for biological control has stimulated several studies into its biology and ecology, including its taxonomy, morphology, reproduction, geographical notes, olfactory system, predator-prey interaction, feeding strategies, mitochondrial genome and microRNAs [ 2 , [4] , [5] , [6] , [7] , [8] , [9] , [10] , [11] , [12] ]. However, the general knowledge about A. custos has important gaps.…”
Section: Introductionmentioning
confidence: 99%